The determination of heavy metals in tap water by using Atomic Absorption Spectroscopy (AAS) / Nor Hasbiyana Abd Wahab - Abd Wahab, Nor Hasbiyana (2008)
Tap water that becomes the main source of water that is used by people should be evaluated for the safety level whether it is free from the contamination of bacteria or heavy metals. Most of the studies that have been done that use tap water samples showed that heavy metals really exist in tap water samples. This study focuses on tap water because it is widely used and it became the basic need for human being. The evaluation of the safety level of tap water is very important. Hence, this study is done to achieve a few objectives , that are to determine the concentration of heavy metals in tap water samples whether they are safe or not according to the parameter and standard of water quality for heavy metals by MNDWQS and US EPA. So as to determine the concentration of each element in order to identify which is the most concentrated and vice versa. This study also compares the level of heavy metals’ concentration according to the types of site sampling from industrial, agricultural and housing areas. By using AAS, the result of this study showed that most of the samples contain heavy metals. This study has achieved all of the objectives whereby the results of this study showed that the levels of most of heavy metals’ concentration exceed the limit for level of the water quality. This study also proves that the location of water might influenced the concentration of heavy metals in tap water sample.